2022
DOI: 10.1186/s12890-022-01934-y
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of anxiety and depression on the prognosis of copd exacerbations

Abstract: Background Frequent and highly prevalent as comorbidities in Chronic Obstructive Pulmonary Disease (COPD) patients, both depression and anxiety seem to have an impact on COPD prognosis. However, they are underdiagnosed and rarely treated properly. Aim To establish the prevalence of depression and anxiety in patients admitted for Acute Exacerbation of COPD (AECOPD) and determine their influence on COPD prognosis. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 42 publications
0
19
1
Order By: Relevance
“…Therefore, there is a need for more experienced psychiatric professionals as well as a well-established system to improve future diagnosis capabilities. On the other hand, in previous studies, psychological scales such as the Hospital Anxiety and Depression Scale (HADS) and Hamilton Anxiety Rating Scale (HAMA) were used to detect AECOPD patients suffering from anxiety and/or depression ( 3 , 8 , 20 ). Accordingly, these studies reported higher prevalence of anxiety and depression than we did (ranging from 44.4 to 68.2%) ( 3 , 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, there is a need for more experienced psychiatric professionals as well as a well-established system to improve future diagnosis capabilities. On the other hand, in previous studies, psychological scales such as the Hospital Anxiety and Depression Scale (HADS) and Hamilton Anxiety Rating Scale (HAMA) were used to detect AECOPD patients suffering from anxiety and/or depression ( 3 , 8 , 20 ). Accordingly, these studies reported higher prevalence of anxiety and depression than we did (ranging from 44.4 to 68.2%) ( 3 , 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety and depression are common in patients with COPD, with an estimated prevalence of 6-74% and 8-80%, respectively (2)(3)(4)(5)(6)(7). As important comorbidities in COPD, anxiety and depression are associated with increased risks of exacerbations (2,8), emergency care use (9), and medical costs (10), contributing to a substantial disease burden of COPD (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following publication of the original article [ 1 ], it was flagged that the authors' respective given and family names had been erroneously swapped in the author list. The author list has since been corrected in the published article and the correct list may be seen in this erratum.…”
Section: Correction To: Bmc Pulmonary Medicine (2022) 22:169 ...mentioning
confidence: 99%
“…COPD patients commonly exhibit some level of depressive symptoms, with depressive symptoms being in 16–74% of them, and the symptoms are commonly unrecognized and thus go untreated [ 6 ]. The unrecognized depressive symptoms are a major clinical challenge as they can adversely affect physical health, quality of life, and prognosis of COPD individuals [ 7 , 8 ]. Depressive symptoms are complex and often change dynamically with the passage of time, with many patients exhibiting few or no depressive symptoms consistently, whereas a minority report persistent symptoms [ 9 ].…”
Section: Introductionmentioning
confidence: 99%